An Analysis of Air Flow at Various Spacing of Fans on a Physical Model of a Road Tunnel - Jandacka, Jozef; Papucik, Stefan; Dekys, Vladimir; Melicher, Richard (Communications - Scientific letters of the University of Zilina, 2008)
In this article, the influence of a jet fan spacing in a longitudinal air conditioning system in a road tunnel on a physical model of the tunnel is analyzed. The analysis of air transport on a physical model with a length of 30 metres was accomplished for various combinations of the connection of 8 jet fans (parallel connection of 8 fans, combined connection of 2 X 4 parallel fans, combined connection (of) 4 X 2 parallel fans and serial connection of 8 fans). From the analysis of measurement on the physical model follows what a big influence the fan spacing has on the speed profile, which to a great extent influences air transport in the tunnel. Our contribution deals with the interpretation of vibration data from the point of view of vibration sources identification. These sources are searched and evaluated from the measured data using a frequency and phase spectrum.